Far from neutral: Research ethics committees, interdisciplinarity and fieldwork - Halkias, Alexandra (Anthropology today, 2024)
This article critiques research ethics committees (RECs) for stifling social sciences research through rigid, one‐size‐fits‐all ethics protocols. It highlights how these protocols, rooted in medical science perspectives, ignore the complexities of fieldwork, and prioritize institutional protection over knowledge advancement. The article illustrates the bureaucratic barriers to sociological and gender studies research through a case study involving fieldwork in a Greek hospital, showing how intersecting hierarchies in the field can render REC instruments invasive or moot. This article aims to enrich academic enquiry by acknowledging the diverse realities of research subjects and methodologies.